Modulation of Functional Connectivity Between Dopamine Neurons of the Rat Ventral Tegmental Area in vitro - van der Velden, Luuk; Vinck, Martin A.; Werkman, Taco R.; Wadman, Wytse J. (Frontiers in Integrative Neuroscience, 2019)
Micro Electrode Arrays were used to simultaneously record spontaneous extracellular action potentials from 10-30 dopamine neurons in acute brain slices from the lateral Ventral Tegmental Area (VTA) of the rat. The spike train of an individual neuron was used to characterize the firing pattern: firing rate, firing irregularity and oscillation frequency. Functional connectivity between a pair of neurons was quantified by the Paired Phase Consistency (PPC), taking the oscillation frequency as reference. Under baseline conditions the PPC was significantly different from zero and 42 of the 386 pairs of VTA neurons showed significant coupling. 50%of the recorded dopamine neurons were part of the coupled VTA network. Raising extracellular potassium from 3.5 mM to 5 mM increased the mean firing rate of the dopamine neurons by 45%. The same increase could be induced by bath application of 300 uM glutamate. High potassium reduced the PPC, but it did not change during the glutamate application. Our findings imply that manipulating excitability has distinct and specific consequences for functional connectivity in the VTA network that cannot be directly predicted from the changes in neuronal firing rates. Functional connectivity reflects the spatial organization and synchronization of the VTA output and thus represents a unique element of the message that is sent to the mesolimbic projection area. It adds a dimension to pharmacological manipulation of the VTA micro circuit that might help to understand the pharmacological (side) effects of e.g. anti-psychotic drugs.